Evaluation of Students’ Communication Skills and Academic Performance in the University of Baghdad - Jasim, Basima; Khalifa, Mohammed (Iraqi National Journal of Nursing Specialties, 2019)
Objective(s): To evaluate students’ communication skills and their academic performance; to compare between the students relative to communication skills and their academic performance in the University of Baghdad and to identify the relationship between students’ communication skills, academic performance and their socio-demographic characteristics of age, gender, grade and socioeconomic status. Methodology: A descriptive design, using the evaluation approach, is carried through the present study to evaluate colleges’ students’ communication skills and their academic performance in the University of Baghdad for the period of January 7th 2019 to August 28th 2019. A non-probability, purposive sample, of (80) university students, is selected. Two questionnaires are utilized; the first iscontained of (15) items that measure the students’ communication skills and the second is comprised of (14) items that measure the students’ academic performance. Reliability and validity of the questionnaires are determined through pilot study. Data are collected through the use of study instruments and the structured interview technique as means for data collection. Data are analyzed through the application of the descriptive data analysis approach which includes frequency, percent and total scores and ranges and inferential statistical data analysis of approach of Multiple Linear Regression. Results: The study indicates that most of the students have fair level of Communication Skills (69%) and fair level of academic performance (67%). Students’ communication skills is influenced by their age and education stage and students’ academic performance is affected by their socioeconomic status. Recommendations: The study recommends that college students should be very well aware of the importance of communication skills and academic performance. Colleges’ curriculum should contain at least one course about communication skills and academic performance. Further research can be conducted on the same topic with wide-range sample size.